Cerebral Aneurysm Pulsation: Do Iterative Reconstruction Methods Improve Measurement Accuracy In Vivo? - Illies, T.; Säring, D.; Kinoshita, M.; Fujinaka, T.; Bester, M.; Fiehler, J.; Tomiyama, N.; Watanabe, Y. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Electrocardiogram-gated 4D-CTA is a promising technique allowing new insight into aneurysm pathophysiology and possibly improving risk prediction of cerebral aneurysms. Due to the extremely small pulsational excursions (<0.1 mm in diameter), exact segmentation of the aneurysms is of critical importance. In vitro examinations have shown improvement of the accuracy of vessel delineation by iterative reconstruction methods. We hypothesized that this improvement shows a measurable effect on aneurysm pulsations in vivo. MATERIALS AND METHODS: Ten patients with cerebral aneurysms underwent 4D-CTA. Images were reconstructed with filtered back-projection and iterative reconstruction. The following parameters were compared between both groups: image noise, absolute aneurysm volumes, pulsatility, and sharpness of aneurysm edges. RESULTS: In iterative reconstruction images, noise was significantly reduced (mean, 9.8 ± 4.0 Hounsfield units versus 8.0 ± 2.5 Hounsfield units; P = .04), but the sharpness of aneurysm edges just missed statistical significance (mean, 3.50 ± 0.49 mm versus 3.42 ± 0.49 mm; P = .06). Absolute volumes (mean, 456.1 ± 775.2 mm3 versus 461.7 ± 789.9 mm3; P = .31) and pulsatility (mean, 1.099 ± 0.088 mm3 versus 1.095 ± 0.082 mm3; P = .62) did not show a significant difference between iterative reconstruction and filtered back-projection images. CONCLUSIONS: CT images reconstructed with iterative reconstruction methods show a tendency toward shorter vessel edges but do not affect absolute aneurysm volumes or pulsatility measurements in vivo. AIDRadaptive iterative dose reductionIRiterative reconstructionFBPfiltered back-projectionHUHounsfield units